Penerapan Digital Marketing untuk Meningkatkan Daya Saing UMKM di Desa Sambongari, Kecamatan Weleri, Kabupaten Kendal - Siti Solikha; Ivana Salsyabila (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This research aims to improve effective digital marketing strategies. In addition, digital marketing provides the necessary training and guidance, so that digital marketing can improve MSME products. This research uses a community service method with assistance and training that ends with an evaluation of effectiveness. The results of this study indicate that the use of digital marketing can increase market reach for products owned by MSMEs in Sambongsari Village. Training and guidance to help MSMEs by implementing digital marketing strategies begins with attractive product photos, logo creation, map creation, social media marketing, search engine optimization (SEO) and content marketing. An increase in sales after implementing the strategies taught will continue to be reported. The application of digital marketing has proven effective in improving MSMEs in Sambongsari Village. The community service work program called Programmed Independent Initiative Real Work Lecture (KKN MIT-18) Posko 26 UIN Walisongo Semarang provides benefits to MSMEs, because it facilitates understanding and application of digital marketing. Some things that MSME players should continue to learn such as changing MSME strategies and seeing the impact of long-term digital marketing implementation